Influence of prestress level on NSM CFRP laminates for the flexural strengthening of RC beams - Rezazadeh, M. (2014)
This study presents an experimental program to evaluate the influence of the prestressing technique on the flexural behavior of reinforced-concrete (RC) beams strengthened with near-surface-mounted (NSM) carbon-fiber-reinforced-polymer (CFRP) laminates. The experimental program was organized to highlight the benefits of this technique for flexural strengthening of RC beams with low reinforcement ratio, susceptible of not respecting serviceability-limit-state (SLS) conditions, namely the deflection limit. For this purpose, five RC beams were fabricated to be tested under monotonic four-point loading. One beam was kept unstrengthened as a control beam, and another one was strengthened with a non-prestressed NSM CFRP laminate. The remaining beams were reinforced with a NSM CFRP laminate prestressed at 20%, 30% and 40% of its nominal tensile strength. Based on the results, applying the prestress force provided an increase of load carrying capacity corresponding to the concrete cracking and steel yielding initiations compared to the non-prestressed strengthened beam. Moreover, the influence of prestress level on the prevailing failure mode of the tested beams was assessed, and the relevant results are presented and discussed. An advanced numerical strategy was also developed to simulate the tested beams, which was demonstrated capable of being used for the design of this type of structures.